PROFIL KONFLIK KOGNITIF DENGAN INTERVENSI DALAM PEMAHAMAN ALJABAR MAHASISWA POLITANI PANGKEP - Sari, Anita (STKIP Andi Matappa, 2020)
The study aims at obtaining information on the profile of cognitive conflict of students by giving intervention on understanding Algebra of students at Pangkep State Polytechnic of Agriculture. The research method employed descriptive qualitative. This study involved the students who experienced cognitive conflict as a sample. The instruments used in collecting the data were written test and interview. Setiap mahasiswa selesai menyampaikan jawaban, akan diberikan informasi baru yang dapat memicu terjadinya konflik kognitif. Each of the students delivered his or her answer: he or she would be given new information that could trigger cognitive conflict. The results of the study reveal that (1) the students experienced cognitive conflict in determining set of completion on inequality that did not have a zero divisor. Based on students understanding, quadratic inequality that difficult to be factored or the factors were not integers that did not have solutions, (2) the students experienced cognitive conflict in solving equation that had infinite solutions. The students tended to work procedurally without identifying relational elements formed by the expressions. The subjects did not see the objects produce in first step that showed experession on the left was equal to the expression on the right side, (3) the students experienced cognitive conflict in determining set of completion on inequality after giving intervention with new information by talking squares on inequality segment, (4) cognitive conflict happened as well on conceptual understanding of correlation between dengan